HUMAN CAPITAL INVESTMENT AND ITS INFLUENCE ON WORKFORCE STABILITY: INSIGHTS FROM TOP-TIER IT COMPANIES - Rekha. R; V. Senthilkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The role of human capital management is an elevating imperative for society. Learn more about the need for human capital management in many top companies in the IT sector. The main aim of the study is to identify the role of human capital management on retention of employees in top IT companies and analyse a new strategy of employee retention in top 5 companies.30 respondents in each company and totalling 150 respondents have been taken. Factor analysis was done using the SPSS tool. The table, and plot were prepared using SPSS software. Human capital management role and strategy of employee return has been prepared using an infographic tool.The main finding that effective employment retention strategy is to introduce career development programs and provide training, compensation and fairness to staff. The main suggestions that Each company will improve their productivity to each of the more motivated and relaxing workers.